2013
DOI: 10.4149/av_2013_01_35
|View full text |Cite
|
Sign up to set email alerts
|

Multiple amino acid mutations in viral RNA polymerase may synergistically enhance the transmissibility and/or virulence of the 2009 pandemic influenza (H1N1) virus

et al.

Abstract: Summary. -Influenza viruses may change their transmissibility and virulence via single or multiple point mutations in the functional regions of their structural proteins. In this study, we compared sequences of all three subunits of viral RNA polymerase, i.e. PA, PB1 and PB2, of the 2009 pandemic influenza A (H1N1) virus isolates from different stages of the pandemic and found that the frequencies of three mutations, including V14I and K716Q in PA and K736G in PB1, showed a similar trend. Interestingly, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Our work suggests that changes to internal viral proteins, including NS1 and PA, occurred during evolution of the third-wave viruses and adapted them for increased replication in human cells. Others have also recently suggested that mutations have occurred in the virus polymerase, since its transfer to humans may enhance replication or transmission ( 56 , 57 ). These previously described mutations may contribute to some of the enhanced polymerase activity we measured for the A/687 third-wave virus polymerase, but our in vitro polymerase reporter system also indicated that the N321K amino acid change in the PA protein, not previously reported, drove enhancement of viral polymerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our work suggests that changes to internal viral proteins, including NS1 and PA, occurred during evolution of the third-wave viruses and adapted them for increased replication in human cells. Others have also recently suggested that mutations have occurred in the virus polymerase, since its transfer to humans may enhance replication or transmission ( 56 , 57 ). These previously described mutations may contribute to some of the enhanced polymerase activity we measured for the A/687 third-wave virus polymerase, but our in vitro polymerase reporter system also indicated that the N321K amino acid change in the PA protein, not previously reported, drove enhancement of viral polymerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Many HPAI H5 viruses can enter host cells, but they cannot replicate successfully owing to the difference in amino acids at position 627 of PB2 protein, namely glutamic acid in AIVs and lysine in human influenza virus 96 . Hence, mutations in the RBD domain may only affect receptor binding and cell entry of AIVs, while replication efficiency of the virus in cells must be assisted by other viral proteins, such as PA, PB1, PB2, and NA, to gain successful cross-species transmission 97 . Therefore, mutations in these proteins and homologous recombination between strains deserve more attention.…”
Section: Introductionmentioning
confidence: 99%